0581 Characteristics of US Women Veterans with Sleep Apnea: Results of a National Survey of VA Healthcare Users. (27th May 2020) - Zhu, R; Carlson, G; Kelly, M; Song, Y; Fung, C H; Mitchell, M N; Josephson, K R; Zeidler, M R; Badr, M S; Alessi, C A; Washington, D L; Yano, E M; et al.
Abstract: Introduction: Sleep apnea (SA) is the most commonly diagnosed sleep disorder among patients in the US Veterans Administration (VA). The dramatic rise in women receiving VA care makes it essential to understand the presentation and treatment of SA in women Veterans. We performed a nationwide survey about sleep among US women Veterans and compared characteristics of respondents with and without a self-reported history of SA diagnosis and treatment. Methods: A survey was mailed to a random sample of 4000 women VA healthcare users. The survey included demographics, Insomnia Severity Index (ISI), Patient Health Questionnaire-4 (PHQ-4 depression/anxiety), Primary Care-Post-Traumatic Stress Disorder (PC-PTSD), RLS symptom presence, SA symptoms (snore loudly, observed breathing pauses), diagnosis of SA, and use of PAP therapy (APAP, BPAP, CPAP). We compared women with and without SA, and (among those with SA) women who did and did not use PAP, using Chi-square and t-tests. Results: 1, 498 completed surveys were returned (mean age 51.6 years, range 18-105 years, 62% non-Hispanic White). 200 respondents (13.4%) reported diagnosed SA. Women with SA were older (p<.001), likely to be employed (p=.013), more likely to snore loudly (p<.001) and to have breathing pauses while asleep (p<.001). They also had higher ISI (p<.001), were more like to report RLS (p<.001) nightmares (p=.027), and had higher PHQ-4 (p<.001) and PC-PTSD (p<.001) scores. Among women with SA, 130 (65%) used PAP. Loud snorers (p<.001) and those with observed breathing pauses were more likely to use PAP (p<.001). Conclusion: One in 7 women who receive VA care report diagnosed SA. Women with SA had more mental health symptoms and comorbid sleep problems. Most reported using PAP therapy, although the amount of use is unknown. Those with SA symptoms were more likely to use PAP. Future work is needed to understand barriers to diagnosis and treatment of SA among women Veterans. Support: Funding: VA Quality Enhancement Research Initiative RRP12-189 (Martin); NIH/NHLBI K24 HL143055 (Martin).